Hybrid multi power sources PEMFC/battery/supercapacitor real time setup energy conversion system - Riad Moualek; Nacereddine Benamrouche; Nabil Benyahia; Amar Bousbaine (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This paper presents an energy management system with multiple sources. The proton exchange membrane fuel cell as the main power drive source is used when needed. However, because of its slow rate it is combined with a battery and supercapacitor racks as secondary sources. The proposed energy conversion system ensures the energy demand of an electric vehicle. The storage system, which includes a battery and a supercapacitor, provides a high level of performance in both autonomy and availability of power. The battery as a primary storage source, feeds the whole system during cruse processes. At needs and during accelerations phases, the supercapacitor, takes over and reacts to supply the load. This topology keeps the fuel cell disconnected from the bus supply, until the battery reaches a critical voltage level. At this time, the fuel cell kicks in and charges the battery rack. The entire system was initially tested using MATLAB/Simulink environment and the outcome findings were subsequently analyzed. The simulated results have been corroborated experimentally using a test rig based on dSPACE real time interface. Experimental results indicate that the suggested approach is capable of meeting the electric vehicle energy requirements.